Promoting organizational success with effective competitive strategy: Examination and analysis of competitive strategies of IBM and DELL within the IT Industry - Kwadade-Cudjoe, Francis (Archives of Business Research, 2020)
Achieving organizational success has always been the bane of businesses, but it is an important requirement for every business. The best approach to achieving this success is to develop a good and effective strategy; the modus operandi for organizational success to achieving competitive advantage. Most organizations work tirelessly to establish strategies to enable the achievement of goals and objectives, but understanding what entails in establishing effective strategies has never been easy. However, once the resources of the organization are identified, and putting together concrete activities to perform on the resources, an effective competitive strategy could be established, which should lead to competitive advantage. Sustaining an organizational competitive advantage is very necessary, so as to create an enabling environment for sustainability, and in addition profitability, whilst pursuing its functions. Fact is, a lot of capital is always expended before a business is founded, and this investment cannot be squandered, but be recouped. Therefore, structuring an effective competitive strategy at the very beginning, is a must for every organization. The generic competitive strategies are cost leadership, differentiation and niche / focus.